Searching for the Oldest Baobab of Madagascar: Radiocarbon Investigation of Large Adansonia rubrostipa Trees - Patrut, Adrian; von Reden, Karl F.; Danthu, Pascal; Leong Pock-Tsy, Jean-Michel; Patrut, Roxana T.; Lowy, Daniel A. (PLoS ONE, 2015)
We extended our research on the architecture, growth and age of trees belonging to the genus Adansonia, by starting to investigate large individuals of the most widespread Malagasy species. Our research also intends to identify the oldest baobabs of Madagascar. Here we present results of the radiocarbon investigation of the two most representative Adansonia rubrostipa (fony baobab) specimens, which are located in south-western Madagascar, in the Tsimanampetsotse National Park. We found that the fony baobab called â€œGrandmotherâ€ consists of 3 perfectly fused stems of different ages. The radiocarbon date of the oldest sample was found to be 1136 Â± 16 BP. We estimated that the oldest part of this tree, which is mainly hollow, has an age close to 1,600 yr. This value is comparable to the age of the oldest Adansonia digitata (African baobab) specimens. By its age, the Grandmother is a major candidate for the oldest baobab of Madagascar. The second investigated specimen, called the â€œpolygamous baobabâ€, consists of 6 partially fused stems of different ages. According to dating results, this fony baobab is 1,000 yr old. This research is the first investigation of the structure and age of Malagasy baobabs.